The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/ps.6742
|View full text |Cite
|
Sign up to set email alerts
|

A fungal Bipolaris bicolor strain as a potential bioherbicide for goosegrass (Eleusine indica) control

Abstract: BACKGROUND: Tea, one of the most important commercial crops on earth, is strongly affected by weeds on productivity and quality. Bioherbicides are shedding new light on weed control in tea gardens in an economical and safe manner.RESULTS: A pathogenic strain SYNJC-2-2 was isolated from diseased leaves of a noxious weed, goosegrass (Eleusine indica), from a tea garden in Zhejiang Province, China. It was identified as the fungal species Bipolaris bicolor based on the morphological characteristics and phylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Any increase in acidity or alkalinity had no effect on the germination rate of B. bicolor conidia, which constantly had a rate of 30 to 32% (Figure 1b). In contrast to present findings, Xiao et al (2021) reported that the optimum pH for conidial germination of B. bicolor was 7 whereas high acidity and alkalify at pH 4 and pH 10, respectively could reduce the conidial germination rate substantially…”
Section: Effects Of Temperaturecontrasting
confidence: 99%
See 2 more Smart Citations
“…Any increase in acidity or alkalinity had no effect on the germination rate of B. bicolor conidia, which constantly had a rate of 30 to 32% (Figure 1b). In contrast to present findings, Xiao et al (2021) reported that the optimum pH for conidial germination of B. bicolor was 7 whereas high acidity and alkalify at pH 4 and pH 10, respectively could reduce the conidial germination rate substantially…”
Section: Effects Of Temperaturecontrasting
confidence: 99%
“…The present findings on the optimal temperature, pH and photoperiod for conidial germination of B. bicolor do not align with the results of Xiao et al (2021). These discrepancies could be attributable to diverse geographic regions, potentially reflecting adaptation of the fungal pathogen (Kumar et al, 2010).…”
Section: Effects Of Photoperiodcontrasting
confidence: 98%
See 1 more Smart Citation
“…A Bipolaris bicolor strain was isolated from severely diseased leaves of goosegrass (Eleusine indica) in a tea plantation system. Further tests on pathogenicity and host range demonstrated the potential of this strain as a biocontrol agent against Poaceae weeds in tea and broadleaf vegetable production (40). The initial field collection of 10 candidate isolates was obtained from 16 tea plantations through a time-consuming process.…”
Section: Microbial Biocontrol With Bioherbicide Agentsmentioning
confidence: 99%
“…Goosegrass ( Eleusine indica L. Gaertn) is one of the top 10 herbicide-resistant weed species distributed throughout the world [ 8 , 9 ]. Although multiple resistances to paraquat, glufosinate, and glyphosate in goosegrass have been reported, the underlying molecular mechanism of herbicide stress responses remains unclear [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%